Passive single-station techniques applied for dynamic characterization of reinforced concrete buildings - Davide Prati; Lorenzo Badini; Giovanni Mochi; Silvia Castellaro; Annarita Ferrante (Tema, 2020)
This work aims to better understand and improve the dynamic characterization of concrete frame buildings through the combined use of finite element modeling and applied seismology. The behavior of the FEM model is compared with values obtained directly in situ through non-invasive tests based on a sensor capable of detecting the seismic microtremor and provide direct information in terms of oscillation periods and displacements. The case study structure was measured using a seismometer, and, at the same time, modeled using SAP2000. By starting from extremely different initial data, multiple variations were made to the model to produce an increase in frequency, aligning it with the one detected instrumentally.